Organocatalytic Cascade Reaction of Aliphatic Enals and Benzoylnitromethane: Synthesis of Enantioenriched Tetrasubstituted Cyclohexene Carbaldehyde - Fredy A. David Rodriguez; Mauricio Maldonado Villamil; James Guevara-Pulido (Journal of Chemistry)
A new example of the reactivity of enals with benzoylnitromethane was studied in a Michael-Michael-Aldol-Dehydration quadruple organocascade reaction. The reaction unexpectedly yielded a tetrasubstituted cyclohexene carbaldehyde with excellent enantiomeric excess when crotonaldehyde was used as the Michael-acceptor, whereas using (E)-Hex-2-enal as the Michael-acceptor formed a cyclic hemiacetal by steering the reaction into the intramolecular formation of the same intermediate via a Michael-Heterocyclization domino reaction.